KOMPARASI HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN PROBLEM SOLVING DAN PROBLEM POSING PADA SISWA KELAS IV SD SWASTA RAMA SEJAHTERA KOTA MAKASSAR - ERWIN NURDIANSYAH; DINAR RIADDIN (De Fermat : Jurnal Pendidikan Matematika, 2020)
This type of research is an experimental study involving two groups given different treatments. This study aims to find out (1) how much the mathematics learning outcomes of fourth grade students of Makassar City Rama Sejahtera Private Elementary School were taught using a problem solving approach, (2) How much the mathematics learning outcomes of fourth grade Rama Sejahtera Private Elementary School Makassar were taught using the problem posing approach, (3) There is a difference between the results of mathematics learning in fourth grade students of Rama Sejahtera Private Elementary School in Makassar City between those taught using a problem solving approach and those taught using a problem posing approach. The population of this study was fourth grade students of Makassar City Rama Sejahtera Private Elementary School in the even semester 2018/2019 which consisted of 3 classes and 2 randomly selected classes as the research sample. Data collection techniques were carried out using learning outcomes tests (pretest and posttest) and observation sheets. The collected data was analyzed using descriptive and inferential statistical analysis techniques. The results obtained from descriptive statistical analysis are: (1) Mathematics learning outcomes of students taught by using problem solving approaches are in the high category with an average of 73.36 and standard deviation of 10.20 of the ideal score of 100. (2) Learning outcomes Mathematics students taught by the problem posing approach are in the low category with an average of 67.96 and standard deviation of 8.29 from the ideal score of 100. From the results of inferential statistical analysis it can be concluded that the mathematics learning outcomes of students taught by problem solving approaches are different from mathematics learning outcomes of students taught by using the problem posing approach.